Genome-Wide Identification and Expression Profiling of Tomato Hsp20 Gene Family in Response to Biotic and Abiotic Stresses - Yu, Jiahong; Cheng, Yuan; Feng, Kun; Ruan, Meiying; Ye, Qingjing; Wang, Rongqing; Li, Zhimiao; Zhou, Guozhi; Yao, Zhuping; Yang, Yuejian; Wan, Hongjian (Frontiers in Plant Science, 2016)
The Hsp20 genes are involved in the response of plants to environment stresses including heat shock and also play a vital role in plant growth and development. They represent the most abundant small heat shock proteins (sHsps) in plants, but little is known about this family in tomato (Solanum lycopersicum), an important vegetable crop in the world. Here, we characterized heat shock protein 20 (SlHsp20) gene family in tomato through integration of gene structure, chromosome location, phylogenetic relationship, and expression profile. Using bioinformatics-based methods, we identified at least 42 putative SlHsp20 genes in tomato. Sequence analysis revealed that most of SlHsp20 genes possessed no intron or a relatively short intron in length. Chromosome mapping indicated that inter-arm and intra-chromosome duplication events contributed remarkably to the expansion of SlHsp20 genes. Phylogentic tree of Hsp20 genes from tomato and other plant species revealed that SlHsp20 genes were grouped into 13 subfamilies, indicating that these genes may have a common ancestor that generated diverse subfamilies prior to the mono-dicot split. In addition, expression analysis using RNA-seq in various tissues and developmental stages of cultivated tomato and the wild relative Solanum pimpinellifolium revealed that most of these genes (83%) were expressed in at least one stage from at least one genotype. Out of 42 genes, 4 genes were expressed constitutively in almost all the tissues analyzed, implying that these genes might have specific housekeeping function in tomato cell under normal growth conditions. Two SlHsp20 genes displayed differential expression levels between cultivated tomato and S. pimpinellifolium in vegetative (leaf and root) and reproductive organs (floral bud and flower), suggesting inter-species diversification for functional specialization during the process of domestication. Based on genome-wide microarray analysis, we showed that the transcript levels of SlHsp20 genes could be induced profusely by abiotic and biotic stresses such as heat, drought, salt, Botrytis cinerea, and Tomato Spotted Wilt Virus (TSWV), indicating their potential roles in mediating the response of tomato plants to environment stresses. In conclusion, these results provide valuable information for elucidating the evolutionary relationship of Hsp20 gene family and functional characterization of the SlHsp20 gene family in the future.